Theoretical study of the interfacial properties of carbon nanotube/epoxy resin nanocomposites. (1st May 2022) - Serizawa, Yurika; Yayama, Tomoe; Akagi, Fumiko
Abstract: We demonstrate the effect of defects in carbon nanotubes (CNTs) on the interfacial interaction of CNT/epoxy nanocomposites by first-principles calculation. Atomistic interface models consisting of single-walled CNT and epoxy (diglycidyl ether of bisphenol A; DGEBA) were used. Total energy, the partial density of states, and electronic charge distributions were investigated. The results indicated a weak interaction between the defect-free CNT and the epoxy. When the DGEBA was placed over the site nearest to the defect on a CNT, it was found to be energetically stable. Moreover, shared charge density, which may result in a stronger interfacial interaction, was observed between the CNT and DGEBA. The presence of the defects is responsible for providing the valence electrons that do not participate in the carbon–carbon bond in the CNTs. Consequently, we conclude that the defects in the CNT are sometimes useful and may enhance interfacial adhesion at the interface of nanocomposites.